Theoretical, Legal and Practical Aspects of Preventing the Crime of Taking a Person Hostage - Annakulov, Azamat (Indonesian Journal Publisher, 2025)
This article examines the theoretical, legal, and practical aspects of the crime of taking a person hostage. It explores the criminological characteristics of hostage-taking offenses, the underlying causes of such crimes, the activities of law enforcement agencies, and effective methods for combating this form of criminality. Special attention is given to the threat posed by these crimes to public security, the role of information and communication technologies in their prevention, and the importance of legal awareness and advocacy in mitigating their occurrence. The study also evaluates current national legislation and international legal standards regarding hostage-taking, comparing their implementation and effectiveness. Additionally, the paper addresses challenges faced in detecting and investigating such crimes, especially in the context of organized crime and terrorism. Practical recommendations are proposed to strengthen institutional cooperation, improve preventive strategies, and enhance public education on legal norms. The findings of the research are intended to support the development of more effective legal and policy frameworks aimed at reducing the incidence of hostage-taking and protecting fundamental human rights and freedoms.